NAMA GALARAN (JULUKAN) PADA MASYARAKAT BANJAR DI KAMPUNG MANDI KAPAU KECAMATAN KARANG INTAN - NFN Jahdiah (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2018)
Nickname is a name used to call someone directly or indirectly. This study specially discusses many kind of nicknames used on Banjar sociey. The aim of this study is to describe the form of nickname used in Banjar society. This study uses sociolinguistic approach. The data collection and method used in this study are dialogue method, continued with provocating, recording, and note taking technique. The data analysis is done through several steps, they are 1) identifying the nickname, 2) classifying the nickname base on positive and negative sense of meaning, 3) interpreting the nickname. The result shows that there are seven nicknames on Banjar society, they are 1) base on physically condition, 2) similarity, 3) event, 4) origin, 5) occupation, 6) attitude, 7) the parent’s name. Sense of meaning in this nickname can be in positive and negative meaning.